the Evaluation of the nootropic activity of the chlorogenic acid present in coffee for the preventive treatment of neurodegenerative diseases: Nootropic Activity of Coffee Pulp Extract (Coffea arabica) - Molina Jaramillo, Elda (2021)
The increase in neurodegenerative diseases has led to the search for products with nootropic activity as adjuvants for the prevention or treatment of these pathologies. In this study, we aim to evaluate the nootropic activity of the extract coffee pulp (Coffea arabica) in small mammals. In the first phase, total phenols were quantified from the coffee samples with the Folin-Ciocalteu method by using both dynamic and assisted maceration. Data were analyzed using ANOVA and Duncan's post-hoc test. In the second phase, twenty-four mice (Mus musculus) of 32.5 g on average were used. These animals were split up into four groups and assigned to one of the following treatments: water as negative control, Ginkgo Biloba as positive control, and two doses of coffee pulp extract. The mice were subjected to training and learning tests in the eight-arm-radial and Morris’s aquatic labyrinth. The latency-time and time that each mouse takes to visit the eight arms of the labyrinth were recorded. The extract of arabica coffee pulp reflects nootropic activity, whose dose 100 mg/kg of weight/day of chlorogenic acid (ACG) contributes to the improvement of cognitive properties.